Multiwall carbon nanotube encapsulated Co grown on vertically oriented graphene modified carbon cloth as bifunctional electrocatalysts for solid-state Zn-air battery. (April 2019) - Zhang, Yuanyuan; Sun, Haohao; Qiu, Yunfeng; Ji, Xinyang; Ma, Tiange; Gao, Feng; Ma, Zhuo; Zhang, Baoxi; Hu, PingAn
Abstract: Vertically-oriented graphene (VG) directly grown on carbon cloth serves as unique support for uniform growth of Zif-67 nanocrystals, and subsequent melamine-assisted pyrolysis results in the anchoring of multiwall carbon nanotubes (MWCNTs) encapsulated Co on VG. Systematic measurements indicate that pyridinic N and pyrrolitic N contents decreased from 600 to 900 °C, and the highest metallic Co contents, as well as well-defined MWCNTs were obtained at 800 °C. Taking advantage of the unique hierarchical nanostructures and adjusted compositions, the free-standing electrode shows excellent bifunctional oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) activities. The presence of MWCNTs, metallic Co, active N species and Co-Nx C sites, as well as in-situ formed Co oxides, will synergistically contribute to the electrocatalytic performance. Such free-standing film directly act as air-cathode to construct all solid-state Zn-air batteries (ZABs), showing comparable rechargeability to commercial Pt/C&Ir/C electrocatalysts, and also possessing unique flexibility. Present work opens a new avenue to improve the ORR and OER performance of Zif-67 derived nanomaterials via manipulating the hierarchical structure and chemical compositions, and sheds insights to the understanding of the electrocatalytic mechamism, also promotes the development of solid-state ZABs. Graphical abstract: Image 1